2017
DOI: 10.1002/bbb.1829
|View full text |Cite
|
Sign up to set email alerts
|

Economic, environmental, and social impacts of different sugarcane production systems

Abstract: Mechanization in the sugarcane agriculture has increased over the last few years, especially in harvesting and planting operations, in the Brazilian Center-South region. The consequences of such a technological shift, however, are not fully comprehended when multiple perspectives are considered such as economic aspects, environmental regulations, and social context. The main goal of this study is to generate comprehensive information to subsidize decision-making processes not only in Brazil but also in other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 24 publications
0
37
0
9
Order By: Relevance
“…A clear example of this dynamic competition is observed in the use of bagasse. Research shows that, nowadays, only a small fraction of the total potential of bagasse is used for electricity production in sugarcane refineries, highlighting the potential for biobased electricity production . However, this study shows that under a stringent climate mitigation policy, bagasse for industrial use is favored above bagasse for electricity production.…”
Section: Discussionmentioning
confidence: 74%
“…A clear example of this dynamic competition is observed in the use of bagasse. Research shows that, nowadays, only a small fraction of the total potential of bagasse is used for electricity production in sugarcane refineries, highlighting the potential for biobased electricity production . However, this study shows that under a stringent climate mitigation policy, bagasse for industrial use is favored above bagasse for electricity production.…”
Section: Discussionmentioning
confidence: 74%
“…An interesting observation from Cardoso et al (2018) in their holistic, triple-bottom-line analysis of sugarcane cultivation in Brazil is the two-faced nature of automation-low employment rate on the one hand and a negligible accident/ injury rate on the other. Quite like sugarcane, soybeans are also raw materials for both the food and fuel sectors in Brazil.…”
Section: Agriculture Forestry and Dairy Farmingmentioning
confidence: 99%
“…As Aleisa and Al-Jarallah (2017) and Cardoso et al (2018) have observed, E-LCA needs to be compounded with S-LCA and LCC as the financial and social aspects of any system cannot be overlooked if an analyst wishes to prove feasibility and credibility at a strategic level to decision-makers. In other words, S-LCA helps to set up what could be labelled as an 'inclusive business model' (Thomas et al 2014) which would assume responsibility for the health, safety and wellbeing of workers, the local community, society, the environment and economic development.…”
Section: Strengths and Opportunitiesmentioning
confidence: 99%
“…In Brazil, a transition from manual to mechanical harvesting has been observed in the sugarcane sector, especially in the Center-South region of Brazil. This transition was motivated by legislation prohibiting sugarcane pre-harvesting burning and other economic, social, and environmental issues related to the manual harvesting [1,2]. Nowadays, mechanical harvesting in this region has reached 97% of the crop area [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cardoso et al [1] compared scenarios with manual and mechanical harvesting. In terms of green (non-burned) cane harvesting, mechanization presented lower sugarcane production costs.…”
Section: Introductionmentioning
confidence: 99%